STRUKTUR DAN DISTRIBUSI PENDAPATAN RUMAHTANGGA PETANI LAHAN SAWAH DI JAWA DAN LUAR JAWA - P.S. RACHMAN, HANDEWI; -, SUPRIYATI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005, 2012)
This article following aim to study (1) structure earnings of farmer household of rice field farm in five kabupaten in Java and two kabupaten Off Java, (2) the earnings distribution and bearing of with ownership distribution of farm, and (3) formulating policy suggestion to improve earnings of household. Research use primary data result of survey of farmer household in MH 2000 / 01, MK I and of MK II 2001. Research result indicate that (1) agricultural sector still contribute more than 60% of earnings of household farmer of rice field farm in research area, and paddy farming system have compartment around 21 - 38% in Java and 23 - 41% Off Java to totalizing earnings of household, and there is tendency more and more wide of rice field farm of land holding high more and more level earnings of household, (2) distribution earnings of household in Java and Off Java have heavy Lameness level (Index of Gini >0,5) where mean Lameness level of household compared to heavier Java Off Java, and ( 3) entry of sector non-agriculture in structure earnings of household farmer of rice field farm have negative diffraction to earnings distribution which for example because of the lowering of accessing household to sector is non-agriculture. Implication of finding is important allocation priority of resource of development for relevant agricultural sector still placed forward. In agricultural sector strives the make-up of earnings related to scale efficiency domination of farm of land holding, usage of seed with quality and efficiency marketing and input output. Besides for the reduce of negative diffraction entry of farmer sector to distribution earnings of household in rice field farm area require to be considered to access household into the sector through extension of opportunity of job in sector non-agriculture.
Keywords: Income, Distribution, Farmer’s Household, Rice Field, Jawa and off Jawa